Parametrization of the angular correlation and degree of linear polarization in two-photon decays of hydrogenlike ions - Amaro, Pedro; Fratini, Filippo; Surzhykov, Andrey (Physical review. A, Atomic, molecular, and optical physics, 2012)
The spontaneous two-photon emission in hydrogenlike ions is investigated within the framework of second-order perturbation theory and Dirac's equation. Special attention is paid to the angular correlation of the emitted photons as well as to the degree of linear polarization of one of the two photons, if the second is just observed under arbitrary angles. Expressions for the angular correlation and the degree of linear polarization are expanded in powers of cosine functions of the two-photon opening angle, whose coefficients depend on the atomic number and the energy sharing of the emitted photons. The effects of including higher (electric and magnetic) multipoles upon the emitted photon pairs beyond the electric-dipole approximation are also discussed. Calculations of the coefficients are performed for the transitions 2s1/2→1s1/2, 3d3/2→1s1/2, and 3d5/2→1s1/2, along the entire hydrogen isoelectronic sequence (1≤Z≤100).
Gesehen am 17.05.2018